2021
DOI: 10.1088/1757-899x/1076/1/012109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dynamic amplitude on response of single pile embedded in collapsible soil

Abstract: This paper includes an experiential study of the dynamic response of one pile under the dynamic load that comes from the motor placed on the cover pile called the source of vibration. This study used the effect of the dynamic movement of vibration on a single pile in collapsible soils (gypseous soil) with a gypsum content of 30%. This experiment is performed in the dry and soak state for four slenderness ratios of the pile (12, 17, 22 and 27) and the pile is inserted after preparing the soil layers in a contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The results demonstrated that, in both the dry and soaked conditions, the velocity, acceleration, and displacement amplitude decreased as the pile thinness percentage increased. Additionally, the values of velocity, acceleration, and displacement amplitude were lower in the soaked condition than in the dry condition [11]. Al-Ezzi and Zakaria's (2020) empirical investigation on the dynamic response of a circular foundation examined how it reacted to the dynamic load brought on by the placement of a square-shaped nearby base that is said to be 'a source of vibration' on top of it.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that, in both the dry and soaked conditions, the velocity, acceleration, and displacement amplitude decreased as the pile thinness percentage increased. Additionally, the values of velocity, acceleration, and displacement amplitude were lower in the soaked condition than in the dry condition [11]. Al-Ezzi and Zakaria's (2020) empirical investigation on the dynamic response of a circular foundation examined how it reacted to the dynamic load brought on by the placement of a square-shaped nearby base that is said to be 'a source of vibration' on top of it.…”
Section: Introductionmentioning
confidence: 99%